PENGAWASAN DINAS LINGKUNGAN HIDUP DAN KEHUTANAN (DLHK) TERHADAP KONVERSI LAHAN PERKEBUNAN KELAPA SAWIT DIKAWASAN HUTAN (HPK) KECAMATAN TAPUNG HULU, KAMPAR TAHUN 2023-2024 - Idris, Muhammad; ,, Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Supervision of conversion forest areas aims to monitor and control changes in forest function to other land uses, such as plantations, settlements, or industry. The problem of this research is the conversion of converted forests to oil palm plantations in HPK forest areas. To address this problem, the Riau Province Environmental Agency (DLHK) has conducted patrols, outreach, and supervision of oil palm plantation companies that do not comply with regulations. The purpose of this study was to determine the supervision of the Environment and Forestry Service (DLHK) regarding oil palm plantation land conversion in the forest area of Tapung Hulu District, Kampar, in 2023-2024. Second, to identify factors hindering the Environment and Forestry Service's (DLHK) supervision of oil palm plantation land conversion. This research was conducted in Pekanbaru, specifically at the Riau Province Environmental and Forestry Service office. This study employed qualitative research methods, based on the theory of T. Hani Handoko, who outlined that the monitoring process has five indicators: establishing implementation standards, determining activity implementation measurements, measuring activity implementation, comparing implementation with implementation standards, and taking corrective action if necessary. Two data sources were used: primary and secondary data. Primary data was obtained through interviews and documentation. Secondary data was obtained through several reference sources, including books, journals, theses, regulations, social media, and official websites. The results of this study indicate that monitoring is not yet fully effective. This requires further improvement, including the monitoring function and following up on individuals in oil palm plantations who violate rules and regulations. Keywords: Supervision, Environment and Forestry Service, Conversion Forest